Fuel enhancement of parallel hybrid electric two-wheeler motorcycle - V. Krithika; C. Subramani (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In this paper, design and simulation of a parallel hybrid electric two-wheeler motorcycle (PHETM) by means of continuous variable transmission (CVT) is illustrated. For simulation, the parallel hybrid electric power train model type in MATLAB/ADVISOR is customized. The internal combustion engine (ICE) be supposed to drive at elevated efficiency areas, in order to attain enhanced fuel economy and a reduced amount of emission. Simultaneously, the ICE must not activate at values of low torque areas. For that reason, get better it whilst ICE is ON, a new energy control strategy is proposed. In the new strategy, the electrical machine absorbs the extra torque of the ICE. This article proposes a PHETM system to propel the vehicle efficiently with reduced amounts of emission on comparing witha conventional vehicle. This system includes two modes of operations for achieving the better results known as motoring mode and generating mode. The switching from one mode to other is based on the vehicle speed which is sensed in real time. A drive cycle is generated by running the vehicle in normal and slightly gradient condition and finally the results are compared.